Crystallization and preliminary X-ray crystallographic analysis of subunit F (F1-94), an essential coupling subunit of the eukaryotic V1VO-ATPase from Saccharomyces cerevisiae - Basak, Sandip (2013)
V-ATPases are very complex multi-subunit enzymes which function as proton-pumping rotary nanomotors. The rotary and coupling subunit F (F1-94) was crystallized by the hanging-drop vapour-diffusion method. The native crystals diffracted to a resolution of 2.64 Å and belonged to space group C2221, with unit-cell parameters a = 47.21, b = 160.26, c = 102.49 Å. The selenomethionyl form of the F1-94 I69M mutant diffracted to a resolution of 2.3 Å and belonged to space group C2221, with unit-cell parameters a = 47.22, b = 160.83, c = 102.74 Å. Initial phasing and model building suggested the presence of four molecules in the asymmetric unit.